Evaluation of the Disaster Preparedness School Program at Sekolah Dasar Negeri Baluwarti and Sekolah Dasar Negeri Bangunrejo 1 in Yogyakarta - Afisa Afisa; Sakir Sakir (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This study aims to determine the results of the evaluation of the implementation of the Disaster Preparedness School Program (SSB) as a Disaster Mitigation Step in Yogyakarta City with case studies of SD Negeri Bangunrejo 1 and SD Negeri Baluwarti. This study analyzed four stages, namely context (context), input (input), process (process), and product (results). The results showed that at the stage of context it could be categorized well where SD Baluwarti had fulfilled while SD Negeri Bangunrejo 1 only did not have a program organizational structure. At the input stage, it can be categorized sufficiently where SD Baluwarti only has no specific regulations related to the program and SD Negeri Bangunrejo 1 does not yet have specific regulations and curriculum related to the program. In the process stage, that has been going well where the SSB program is still running, it's just that SD Negeri Bangunrejo 1 is more focused on learning in the classroom while SD Negeri Baluwarti continues to simulate at least one use. At the product stage the SSB program was in line with the objectives of increasing school residents' preparedness for disasters.